2016
DOI: 10.1080/02670844.2016.1145377
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature erosion of Fe-based coatings reinforced with cermet particles

Abstract: High-velocity oxy-fuel sprayed, iron alloy-based powder coatings, reinforced with tungsten carbide-cobalt (WC-Co) and titanium carbide-nickel molybdenum (TiC-NiMo) cermet particles, are compared under high-temperature abrasive-erosive wear conditions. Both WC-Co and TiC-NiMo particles underwent fracture, as well as dissolution, during the spraying process, but in the case of WC-Co particles this process was remarkably less intensive. Under the low impact angle conditions, the WC-Co particle-reinforced coating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Erosion wear is the progressive material loss from a solid surface due to mechanical interaction between the surface and a fluid (multicomponent fluid, impinging liquid, or solid particles) [1]. This wear phenomenon also occurs under high-temperature conditions in various industries such as casting, petrochemical, garbage incineration, and power generation [2][3][4]. High-velocity oxyfuel (HVOF) coatings are commonly applied to mitigate this type of wear by spraying materials such as WC-Co and Cr 3 C 2 -NiCr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erosion wear is the progressive material loss from a solid surface due to mechanical interaction between the surface and a fluid (multicomponent fluid, impinging liquid, or solid particles) [1]. This wear phenomenon also occurs under high-temperature conditions in various industries such as casting, petrochemical, garbage incineration, and power generation [2][3][4]. High-velocity oxyfuel (HVOF) coatings are commonly applied to mitigate this type of wear by spraying materials such as WC-Co and Cr 3 C 2 -NiCr.…”
Section: Introductionmentioning
confidence: 99%
“…High-velocity oxyfuel (HVOF) coatings are commonly applied to mitigate this type of wear by spraying materials such as WC-Co and Cr 3 C 2 -NiCr. However, these materials show operation limits at temperatures of 450-550 • C and 800-900 • C, respectively [4][5][6][7]. For this reason, the use of high-temperature alloys that are Fe-based, Ni-based, and MCrAlY (M=Ni, Co or NiCo), and the mixture of these alloys with different ceramics and cermets such as TiC-NiMo, CrB, Cr 3 C 2 , WC-Co, etc., have been proposed [4,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma-sprayed coating generally consists of overlapping splats which is more or less similar to the morphology of the substrate or to that of previous splats. Plasma-sprayed coatings are usually anisotropic and their erosion rates tend to depend on impact angle [3][4][5][6]. Kingswell et al [7] and Zhang et al [8] have reported that the erosion mechanism in plasmasprayed alumina coating is different from those in bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma-sprayed coating generally consists of overlapping splats which is more or less similar to the morphology of the substrate or to that of previous splats. Plasma-sprayed coatings are usually anisotropic and their erosion rates tend to depend on impact angle [3-6]. Kingswell et al.…”
Section: Introductionmentioning
confidence: 99%
“…Микроструктура и коррозионная стойкость наночастиц Ti, армированных Ni-Ti композитными покрытиями, полученных методом электроосаждения, изучены в [9], электродугового напыления -в [10]. Износостойкость покрытий системы TiC-NiMo и Cr 3 C 2 -Ni, армированных FeCrSiB, полученных методом высокоскоростного газопламенного напыления, обсуждается в [11], а высокотемпературная эрозия покрытий на основе железа, армированных керметными частицами, -в [12]. Исследование микроструктуры и свойств покрытий на стали 45, нанесенных методом электроискрового осаждения электродами на основе TiC-Ni-Mo, произведено в [13].…”
Section: Introductionunclassified